Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Colorectal Peritoneal Metastases: A Systematic Review - Parikh, Manasi S; Johnson, Paul; Romanes, Jonathan Paul; Freitag, Harvey E; Spring, Mary E; Garcia-Henriquez, Norbert; Monson, John R T (Diseases of the colon & rectum, 2022)
Combined treatment modality of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy is emerging as an alternative option for colorectal peritoneal metastases, but there is ambiguity regarding patient selection, treatment protocols, and efficacy. To elaborate on the patient characteristics, hyperthermic intraperitoneal chemotherapy protocol and health outcomes in colorectal peritoneal metastases patients undergoing a combination of hyperthermic intraperitoneal chemotherapy and cytoreductive surgery and provide guidance for future studies. A Medline search for English language studies published between 2004 and 2019. Medical subject headings and key terms, including: hyperthermic intraperitoneal chemotherapy, colorectal peritoneal metastases, colorectal cancer and combinations thereof as per guidelines. Overall survival, disease-free survival, and morbidity and mortality rates. Of the 26 included studies, 42% were published between 2016 and 2019. More than half of the studies were retrospective in nature and conducted in tertiary specialized centers outside of the United States. The median age range was 44 to 62 years. Mitomycin C-based therapy was seen in 50% of studies. Mean weighted median disease-free survival for 11 studies was 15 months (9 to 36 months). Median OS ranged from 12 to 63 months, with an average of 33.6 months among 20 studies. Overall morbidity varied from 11% to 56%, with a weighted mean of 29% in 18 studies. Mortality ranged from 0 to 34%, with a weighted mean of 4% in 15 studies. Despite careful study selection, variability in methodology of the included studies can limit review findings. Due to study heterogeneity, and a recent large, randomized trial showing no overall benefit, use of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy in colorectal peritoneal metastases patients is highly controversial. Further standardized controlled studies can help uniformly define and build consensus among the medical community on patient eligibility and the optimal hyperthermic intraperitoneal chemotherapy techniques. Registered on March 3, 2020, CRD42020146942.